Believe they can succeed, and they will: intrapreneurial behavior and leadership. Issue 3 (23rd February 2021) - Farrukh, Muhammad; Meng, Fanchen; Raza, Ali
Abstract : Purpose: A leader's job is not to put greatness into people, but rather to recognize that it already exists and to create an environment where that greatness can emerge and grow (Smith, 2014). Based on Brad Smith's quote, the purpose of this study is to investigate the role of the leader's expectations, leader-member exchange (LMX) and organizational climate for innovation in fostering the intrapreneurial behavior (IB) of employees. Design/methodology/approach: Data were collected from employees and their supervisors working across industries such as pharmaceutical, chemical, engineering and manufacturing. Collected data were then analyzed using the structural equation modeling technique. Findings: The authors' results show that LMX and leaders' expectations are positively linked to employees' IB. Moreover, this association is mediated by organizational climate. Practical implications: This study's findings contribute to the literature on intrapreneurship and may also help practitioners formulate interventions to foster IB in organizations that will ultimately lead to higher performance. Originality/value: This study attempted to investigate the effect of LMX and the Pygmalion effect on IB through employees' perception of organizational climate for innovation. The literature in this field is scarce and theoretical development is weak because traditional collaborative or participative leadership approaches are more relevant to an outcome than innovation.